Pengaruh Dukungan Keluarga dan Iklim Sekolah terhadap Student Engagement Siswa Sekolah Menengah - Muhibbin, Maulana Arif; hati, Rien Permata; Yusri, Jihan Fadiyah Utami (Penerbit Widina, Widina Media Utama, 2025)
Student engagement is the key to successful student learning in schools. This study aims to determine the effect of family support and school climate on student engagement in learning in secondary schools. The method used is quantitative with multiple linear regression analysis techniques. The measuring instruments used include the student engagement scale, family support scale (FSS), and the Maryland's safety and supportive school instrument to measure school climate. The results of the study on 181 students showed that simultaneously, family support and school climate had a significant effect on student engagement (R² = 0.262 p 0.05). However, partially, only school climate had a significant effect (? = 0.487, p 0.05), while family support did not show a significant effect (p 0.05). These results indicate that a positive school climate can increase student engagement in academic and non-academic activities. Thus, it is important to create a conducive school climate to increase active student participation so that it will improve the quality of learning.ABSTRAKKeterlibatan siswa merupakan kunci sukses pembelajaran siswa di sekolah. Penelitian ini bertujuan untuk mengetahui pengaruh family support dan iklim sekolah terhadap keterlibatan siswa dalam pembelajaran pada sekolah menengah. Metode yang digunakan adalah kuantitatif dengan teknik analisis regresi linear berganda. Alat ukur yang digunakan meliputi student enggagement scale, family support scale (FSS), dan instrumen maryland's safety and supportive school untuk mengukur iklim sekolah. Hasil penelitian terhadap 181 siswa menunjukkan bahwa secara simultan, family support dan iklim sekolah berpengaruh signifikan terhadap keterlibatan siswa (R² = 0,262 p 0,05). Namun secara parsial, hanya iklim sekolah yang memiliki pengaruh signifikan (? = 0,487, p 0,05), sedangkan family support tidak menunjukkan pengaruh yang signifikan (p 0,05). Hasil ini menunjukkan bahwa iklim sekolah yang positif dapat meningkatkan keterlibatan siswa dalam kegiatan akademik dan non-akademik. Dengan demikian penting menciptakan iklim sekolah yang kondusif untuk meningkatkan partisipasi aktif siswa sehingga akan meningkatkan kualitas pembelajaran.